Віртуальна реальність як середовище соціалізації особистості - Борсук, Руслан Олександрович (Протидія дезінформації в умовах російської агресії проти України: виклики і перспективи: тези доп. учасників міжн. наук.-практ. конф. (Анн-Арбор - Харків, 12-13 груд. 2023 р.), 2023)
The theses present the problem of personality socialization in virtual space. The author defines the concept of virtual reality and its features in the context of socialization of the individual. In particular, he notes that virtual reality is a heterogeneous environment, with various tools, platforms and visual forms, which significantly diversifies the behavior and enthusiasm of an individual in the network. The virtual environment has its own characteristics. The author notes the peculiarities of the virtual environment, namely: the language, the system of signs and symbols, the rules and norms of communication, the social hierarchy of the participants or the lack thereof. Virtual reality appears as another valuable and meaningful environment that regulates human actions, forms new algorithms and challenges. Socialization, which occurs through multifaceted interaction, contributes to the development of personality in accordance with the requirements of the modern man-made world. The author hypothesizes that in virtual reality human values acquire recombination. Virtual space not only allows you to play social roles, but also to search for yourself in the world.